POLITICIANS AND JOURNALISTS: IN THE SHADOW OF THE INFORMATION AGENDA - A. M. Ogorodnova (Дискурс, 2016)
Article considers the formation factors of shadow aspects of interaction of politicians and journalists, and the reasons compelling representatives of mass media to participate in reproduction of shadow political and information structure in modern Russia. The author represents the results of questionnaire of journalists participating in the All-Russian forum Taurida in September, 2015 concerning communication problems in their professional activity